2010
DOI: 10.1111/j.1537-2995.2009.02569.x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of a screening assay that identifies the abnormal prion protein PrPTSE in plasma: initial results with 20,000 samples

Abstract: The screening assay was studied in terms of specificity and practicality and was found to be suitable for use in routine testing of blood donations. However, throughput must be enhanced by automation of the assay, and traceability would be improved if automated systems were used to distribute and identify samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Using this assay, Amorfix performed a blind test of 1000 human plasma samples that had been spiked with vCJD-infected or uninfected brain homogenate. Later, Guntz et al (2010) were able to test more than 20 000 plasma samples from French donors. The test was performed with 1 ml of not yet leukoreduced plasma, and PrP aggregates were concentrated from plasma samples and disrupted by denaturation.…”
Section: Amorfix Ep-vcjdmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this assay, Amorfix performed a blind test of 1000 human plasma samples that had been spiked with vCJD-infected or uninfected brain homogenate. Later, Guntz et al (2010) were able to test more than 20 000 plasma samples from French donors. The test was performed with 1 ml of not yet leukoreduced plasma, and PrP aggregates were concentrated from plasma samples and disrupted by denaturation.…”
Section: Amorfix Ep-vcjdmentioning
confidence: 99%
“…The tendency of PrP to aggregate has also been exploited by the developers of the Amorfix EP-vCJD blood screening assay, the first commercially available diagnostic immunoassay (Amorfix Life Sciences Press Release, 2008), which has been re-evaluated for feasibility by the Guntz laboratory (Guntz et al, 2010). Using this assay, Amorfix performed a blind test of 1000 human plasma samples that had been spiked with vCJD-infected or uninfected brain homogenate.…”
Section: Amorfix Ep-vcjdmentioning
confidence: 99%
“…The high-throughput assay achieved 100% sensitivity and specificity on 1,000 blinded human plasma samples, which included samples that were spiked with variant CJD-infected and normal brains [50]. In 2009, the specificity of the method was ascertained on a large-scale screening initiated in France in over 20,000 human blood samples [51]. Results showed that on the first run 486 samples were positive (97.6% specificity), 20 of which were then confirmed positive on a second screening [51].…”
Section: Other Potential Assays For the Detection Of Misfolded Prpmentioning
confidence: 99%
“…In 2009, the specificity of the method was ascertained on a large-scale screening initiated in France in over 20,000 human blood samples [51]. Results showed that on the first run 486 samples were positive (97.6% specificity), 20 of which were then confirmed positive on a second screening [51]. The repeat-reactive samples were finally considered negative on a third screening [51].…”
Section: Other Potential Assays For the Detection Of Misfolded Prpmentioning
confidence: 99%
See 1 more Smart Citation